2017
DOI: 10.1108/srj-11-2015-0172
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the institutional context on sustainability reporting. A cross-national analysis

Abstract: Purpose This paper intends to compare the sustainability reporting (SR) in three different national and institutional contexts, namely Italy, Brazil and USA, and aims to investigate whether companies show a different approach to SR depending on the institutional setting where they operate. Design/methodology/approach To reach this goal, a sample of 150 reports was content-analyzed through a methodology based on a coding process which overcomes part of the limitations in previous works. Findings Results obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 78 publications
1
24
0
5
Order By: Relevance
“…In order to show the relevance of the institutional environment in corporate reporting, we found theoretical support in Institutional Theory [38][39][40], Stakeholders Theory [41,42], and Legitimacy Theory [43]. According to Ali et al [14], this last theoretical approach (Legitimacy Theory) is the dominant theoretical lens in studies of companies from both developed and developing countries.…”
Section: Institutional-level Cg Mechanismsmentioning
confidence: 85%
See 1 more Smart Citation
“…In order to show the relevance of the institutional environment in corporate reporting, we found theoretical support in Institutional Theory [38][39][40], Stakeholders Theory [41,42], and Legitimacy Theory [43]. According to Ali et al [14], this last theoretical approach (Legitimacy Theory) is the dominant theoretical lens in studies of companies from both developed and developing countries.…”
Section: Institutional-level Cg Mechanismsmentioning
confidence: 85%
“…Luoma and Goodstein [47] emphasized the need to understand the institutional environment in which firms operate for a better comprehension of firm strategies and managerial choices in relation to CSR practices and engagement. Following this suggestion, some authors have shown how the differences concerning CSR implementation and performance among organizations from different institutional settings can be explained in terms of the differences in the rules, norms, values, routines, and responsibilities expected [40]. Likewise, CG mechanisms are determined by the institutional environment in which each company has developed its activities [19,30].…”
Section: Institutional-level Cg Mechanismsmentioning
confidence: 99%
“…Further, empirical evidence shows that SRQ is the synthesis of a complex system of elements, including the quantity and type of information disclosed, the managerial orientation of the companies [68], and the credibility of their sustainability reporting practices [69]. Adopting different methods of evaluation, researchers have demonstrated that in the absence of common rules, sustainability reporting practices vary in different countries [70]. Unfortunately, few studies have focused on the variations on SRQ after the implementation of mandatory NFD in a cross-country perspective [9].…”
Section: The Growing Attention To Sustainability Reportingmentioning
confidence: 99%
“…According to some studies, the introduction of new regulatory requirements contributes to the improvement of sustainability reporting quality, and others, on the contrary, provide evidence for no effect [78,82,[97][98][99][100]. There might be at least two reasons explaining this absence of consensus: on the one hand, evidence regarding sustainability reporting practices studied from the institutional theory perspective supports a line of argumentation that proposes that sustainability reporting practices depend on the institutional frameworks in which they are developed [101][102][103][104][105]. Consequently, the design of laws or policies establishing mandatory sustainability reporting might influence in diverse ways the outcomes of sustainability reporting practices.…”
Section: Literature Reviewmentioning
confidence: 99%